Current status of Helicobacter pylori infection and prevalence of resistance-associated gene mutations in Bortala Mongolian Autonomous Prefecture, Xinjiang: a single-center study - Yuan, Gai-Ling; Yang, Jing; Peng, Yan; Lai, Jin-Xin; Li, Zheng-Kang (Frontiers in Microbiology, 2025)
BackgroundHelicobacter pylori (H. pylori), a globally prevalent infectious pathogen, has been epidemiologically associated with dyspepsia, peptic ulcer disease, and gastric carcinogenesis. However, comprehensive regional epidemiological data regarding infection prevalence, antimicrobial resistance patterns, and associated risk factors remain insufficient in the Bortala MongolianAutonomous Prefecture of Xinjiang, China.MethodsA cross-sectional study was conducted from June 4 to June 9, 2023, enrolling 341 participants through systematic sampling in Bortala Prefecture. Diagnostic procedures combined non-invasive urea capsule sampling with genotypic detection techniques for simultaneous H. pylori identification and antimicrobial resistance profiling. Multivariate logistic regression analysis was performed on demographic and behavioral variables obtained through standardized questionnaires.ResultsThe study revealed an H. pylori infection prevalence of 29.03% (99/341; 95% CI: 24.13–34.34%). Genotypic resistance analysis demonstrated resistance rates of 51.52% (51/99; 95% CI: 41.72–61.32%) for clarithromycin and 46.46% (46/99; 95% CI: 36.66–56.26%) for levofloxacin. Female participants showed a marginally elevated infection risk (OR = 1.27, p = 0.35), while communal cup-sharing behavior demonstrated borderline significance as a risk factor (OR = 1.95, p = 0.09). No statistically significant independent risk factors were identified in the multivariate analysis.ConclusionThe Bortala Prefecture exhibits alarming genotypic resistance patterns to first-line antibiotics, despite a moderate H. pylori infection prevalence. These findings underscore the critical need for region-specific antimicrobial stewardship and evidence-based treatment protocols guided by local resistance profiles. Future research should prioritize stratified sampling methodologies to delineate ethnicity-specific risk profiles and validate potential risk factors in larger cohorts.